BILANGAN KROMATIK LOKASI GRAF POHON DAN KARAKTERISASI GRAF DENGAN BILANGAN KROMATIK LOKASI 3 - (NIM: 30108001); Tim Pembimbing: Prof. Dr. Edy Tri Baskoro, Dr. Hilda Assiyatun, dan Dr. Djo, ASMIATI
The locating-chromatic number of a graph was introduced by Chartrand et al. in 2002. This concept is derived from the graph partition dimension and graph coloring. The partition dimension of a graph was firstly studied by Chartrand, Zhang, and Salehi in 1998. They gave the partition dimension for some classes of trees, such as paths, double stars, and caterpillars. Since then, many studies have been conducted to find the partition dimension for the other certain classes of graphs. In this dissertation, we determine the locating-chromatic number of some classes of trees, namely an amalgamation of stars, banana trees, firecrackers, and caterpillars